Analysis of Sharia Financial Literacy Levels of Nagara's Muslim Community - El Wafa, Faqih; Rahmah, Rahmah; Gafur, Abdul; Ansharullah, Ansharullah (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2024)
Purpose: This research was to determine the level of Islamic financial literacy of the Nagara Community, North Daha District, Hulu Sungai Selatan Regency and what factors influence the level of literacy.Design/methodology: This study uses a questionnaire distributed online via google from. The sample used was 100 respondents. The data analysis method used is descriptive statistics and ANOVA test.Findings: The level of Islamic financial literacy of the North Daha District Community is 68% or in the medium category. The test results show that among the four factors (gender, age, education and occupation) education and occupation factors significantly affect Islamic financial literacy.Practical implications: this study can be used as a form of government benchmark to improve Islamic financial literacy, especially in areas that have minimal Islamic financial institutions. With this research, stakeholders can determine what programs are suitable for increasing literacy on indicators that are considered lacking.Originality/Value: This research is carried out using a combined method using the Chen and Volpe theory and collaborated using Islamic financial literacy indicators. In addition, the test results show that the variables of gender and age do not affect the level of literacy